Iron Adequacy During Pregnancy. Issue 3 (May 2018) - Snow, Denise
Abstract : Evaluation of adequate iron intake is an important aspect of prenatal care. Our nutrition expert, Denise Snow, explains how to help pregnant women make sure they are getting enough iron during their pregnancy.